The Influence of Demographic and Economic Factors on Non-Performing Loans of MSMEs in Regional Development Banks - Zulkarnain, Muhammad Aris; Hayat, Atma; Juniar, Asrid (Cita Konsultindo Research Center, 2024)
This study aims to analyze the demographic and economic factors affecting Non-Performing Loans (NPLs) of Micro, Small, and Medium Enterprises (MSMEs) at the South Kalimantan Regional Development Bank. By employing logistic regression analysis, this research seeks to address the primary issue of loan defaults in the banking sector. Building on previous research that identifies various bank-specific and macroeconomic factors influencing NPLs, this study positions itself within the broader discourse by focusing on demographic variables such as age, gender, and economic sector. The methodology involves analyzing MSME loan records from 2020 to 2023, considering variables like loan type, region, loan term, loan limit, inflation, and economic growth. The main findings reveal significant predictors of NPLs, including age, gender, loan term, loan limit, inflation, and economic growth. These results offer novel insights into the determinants of NPLs, suggesting that older borrowers and higher loan limits increase the likelihood of NPLs, while female borrowers, longer loan terms, lower inflation, and higher economic growth reduce it. The study's recommendations for the South Kalimantan Regional Development Bank include incorporating these factors into their credit risk assessments to improve loan performance and financial stability.